2003
DOI: 10.1093/nar/gkg328
|View full text |Cite
|
Sign up to set email alerts
|

RNA helicase A interacts with dsDNA and topoisomerase IIalpha

Abstract: RNA helicase A (RHA) is a multifunctional protein involved in various nuclear processes such as transcription and RNA export. It is believed that the interacting factors play important roles in determining the functional specificity of RHA. Here we show that RHA directly interacts with double-stranded (ds) nucleic acids (NAs) and assembles complexes with topoisomerase IIalpha. First, electrophoresis mobility shift assays demonstrate that RHA interacts with dsDNAs of different lengths ranging from 15 to 104 bp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 51 publications
3
45
0
Order By: Relevance
“…These proteins are highly conserved from viruses and bacteria to humans (26). Although initially classified as RNA helicases, many members of the DExD/H helicase family, including DHX36 and DHX9, were found to display DNA helicase activity (27,28). Sequence analyses revealed that DHX36 and DHX9 are in the same DEAH/RHA helicase subfamily, which is close to but is clearly separated from the RIG-I-like helicase subfamily (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins are highly conserved from viruses and bacteria to humans (26). Although initially classified as RNA helicases, many members of the DExD/H helicase family, including DHX36 and DHX9, were found to display DNA helicase activity (27,28). Sequence analyses revealed that DHX36 and DHX9 are in the same DEAH/RHA helicase subfamily, which is close to but is clearly separated from the RIG-I-like helicase subfamily (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RHA, also known as DHX9, is a 130-kDa protein which belongs to the DEXD/H box family of proteins. Members of this family act as ATP-driven motors and can unwind both double-stranded RNA and DNA (50,51) or control switches at very specific points in processes such as pre-mRNA splicing or during ribosome biogenesis (17). In addition to its helicase activity, with the energy derived from ATP, RHA is able to bind and remodel RNA or RNA-protein complexes and subsequently regulates many aspects of cellular RNA metabolism, such as transcription, RNA nuclear export, and translation initiation (9,17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a core helicase domain, there are also extending N-terminal and Cterminal domains that are thought to be involved in proteinprotein/RNA interactions (20). Although generally believed to contain probable RNA helicase/unwindase activity, some members of the DDX/DHX family, such as DHX9 (also called RNA helicase A), have also been shown to bind DNA and function as a DNA helicase (53). In fact, DEAH RNA helicases contain some degree of structural homology to DNA helicases (13).…”
Section: Discussionmentioning
confidence: 99%